2010
DOI: 10.4103/0259-1162.69306
|View full text |Cite
|
Sign up to set email alerts
|

Conscious sedation for awake craniotomy in intraoperative magnetic resonance imaging operating theater

Abstract: This case report describes the first case in intraoperative magnetic resonance imaging operating theater (iMRI OT) (BrainSuite®) of awake craniotomy for frontal lobe glioma excision in a 24-year-old man undergoing eloquent cortex language mapping intraoperatively. As he was very motivated to take pictures of him while being operated upon, the authors adapted conscious sedation technique with variable depth according to Ramsey's scale, in order to revert to awake state to perform the intended neurosurgical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
“…The included manuscripts mainly consisted of informal (non-systematic) reviews (n=10) [2][3][4][5][6][25][26][27][28][29], institutional experiences (n=10) [30][31][32][33][34][35][36][37][38][39], and case series/retrospective studies (n=12) [40][41][42][43][44][45][46][47][48][49][50][51], with only a few prospective studies (n=4) [52][53][54][55]. We also included 11 references that were published only in abstract form [56][57][58][59][60][61] or case report format [62][63][64][65][66]. Original data pertinent to the topics of interest could be extracted from the case series/ retrospective studies, prospective studies, and from 5 abstracts (see…”
Section: Resultsmentioning
confidence: 99%
“…The largest case series by Kamata et al was published only in abstract format and reported critical events during 365 awake craniotomies [56]. The other 4 references consisted of one abstract describing a single case [65], one case report [64], and 2 smaller case series describing the institutional experience with 42 and 7 cases, respectively [50,63]. The authors noted challenges related to patient positioning, the noise burden during scanning, and the added difficulty of anesthesia management in an iMRI environment while providing care to an awake but inaccessible patient with an unsecured airway.…”
Section: Awake Craniotomy With Imrimentioning
confidence: 99%
See 2 more Smart Citations